Effect of Chemical Enhancers on In Vitro Release of Salbutamol Sulphate from Transdermal Patches - Budhathoki, Uttam; Thapa, Panna (Kathmandu University Journal of Science, Engineering and Technology, 2005)
The effect of combination of PG with DMSO, BC, IPM, Tween 80 and SLS on drug release rate was studied in vitro. The mechanism of drug release was also studied by using power law. Significant difference (One way ANOVA; p<0.05) in release rate among the 16 formulations was seen in the study. The release profiles of various formulations also showed that the added enhancers in individual batches affect the release rate of the drug. The concentration of DMSO and Tween 80 showed directly proportional where as concentration of BC and SLS showed inversely proportional relationship with drug release rate. The increase followed by decrease in drug release rate was seen with increase in IPM concentration. In most of the formulations, drug release occurred by diffusion partially through a swollen matrix and water-filled pores.